FORECAST OF ELECTRICITY DEMAND FOR THE NEXT 5 YEARS IN THE NATIONAL STRATEGIC AREA OF LAKE TOBA IN THE FRAMEWORK OF SUPPORTING NATIONAL TOURISM IN SIMALUNGUN DISTRICT (CASE STUDY OF PARAPAT CITY) - Setiawan, Ben; Wooton, Ian; Florenta Butar-Butar, Diana; Panjaitan, Hadi; Saragih, Jopinus (Universitas Efarina, 2022)
The availability of electric power is an obligation at this time, because the economic and social activities of the people of a region continue to increase. Simalungun Regency is an area in the middle of the island of Sumatra. Simalungun Regency's electricity is currently quite good. On the other hand, the island of Simalungun Regency has a lot of potential from various sectors, especially tourism, especially the Lake Toba area. Both of these require business developers and the government to maintain the continuity of the supply of electrical energy. Problems regarding electricity will arise if there is an imbalance between the electrical energy produced and what is requested by the customer. In order for this problem to be overcome, a strategy is needed, namely forecasting the demand for electrical energy within a certain period of time so that the distribution of electrical energy becomes efficient. Based on data from PT PLN (Persero) for the North Sumatra Region, Parapat City Area, Simalungun Regency, total electricity consumption in 2017 has reached 22,311,374 kWh. By using the econometric method that takes into account the influence of the Gross Regional Domestic Product (GRDP), capable capacity, electrification ratio, it can be known the amount of electricity consumption in the coming year. Based on the results of the calculation of the electricity load forecasting in 2022, the total consumption of electrical energy has reached 46,149,759.6069 KWh which is an increase of around 106.84% from 2017 which comes from four types of customers, namely households, commercial, public and industrial. Based on data from PT PLN (Persero) for the North Sumatra Region, Parapat City Area, Simalungun Regency, total electricity consumption in 2017 has reached 22,311,374 kWh. By using the econometric method that takes into account the influence of the Gross Regional Domestic Product (GRDP), capable capacity, electrification ratio, it can be known the amount of electricity consumption in the coming year. Based on the results of the calculation of the electricity load forecasting in 2022, the total consumption of electrical energy has reached 46,149,759.6069 KWh which is an increase of around 106.84% from 2017 which comes from four types of customers, namely households, commercial, public and industrial. Based on data from PT PLN (Persero) for the North Sumatra Region, Parapat City Area, Simalungun Regency, total electricity consumption in 2017 has reached 22,311,374 kWh. By using the econometric method that takes into account the influence of the Gross Regional Domestic Product (GRDP), capable capacity, electrification ratio, it can be known the amount of electricity consumption in the coming year. Based on the results of the calculation of the electricity load forecasting in 2022, the total consumption of electrical energy has reached 46,149,759.6069 KWh which is an increase of around 106.84% from 2017 which comes from four types of customers, namely households, commercial, public and industrial. By using the econometric method that takes into account the influence of the Gross Regional Domestic Product (GRDP), capable capacity, electrification ratio, it can be known the amount of electricity consumption in the coming year. Based on the results of the calculation of the electricity load forecasting in 2022, the total consumption of electrical energy has reached 46,149,759.6069 KWh which is an increase of around 106.84% from 2017 which comes from four types of customers, namely households, commercial, public and industrial. By using the econometric method that takes into account the influence of the Gross Regional Domestic Product (GRDP), capable capacity, electrification ratio, it can be known the amount of electricity consumption in the coming year. Based on the results of the calculation of the electricity load forecasting in 2022, the total consumption of electrical energy has reached 46,149,759.6069 KWh which is an increase of around 106.84% from 2017 which comes from four types of customers, namely households, commercial, public and industrial.